2007
DOI: 10.1002/path.2137
|View full text |Cite
|
Sign up to set email alerts
|

Selective upregulation and amplification of the lysyl oxidase like‐4 (LOXL4) gene in head and neck squamous cell carcinoma

Abstract: Members of the lysyl oxidase family (LOX) are copper and lysyl-tyrosine quinone cofactor-containing amine oxidases that are important for the assembly and maintenance of components of the extracellular matrix. Our previous results demonstrated that a novel member, LOXL4, is overexpressed in head and neck squamous cell carcinoma (HNSCC) compared to normal squamous epithelium. Results of the current study showed overexpression of the LOXL4 transcript in 74% (46 of 62) of invasive HNSCC tumours and 90% of both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…LOXL4, the least well-characterized family member, is overexpressed in head/neck and colorectal carcinomas (16,17). The HIF → LOXL4 pathway plays a significant role in collagen cross-linking, metastatic niche formation, and metastasis in a subset of breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…LOXL4, the least well-characterized family member, is overexpressed in head/neck and colorectal carcinomas (16,17). The HIF → LOXL4 pathway plays a significant role in collagen cross-linking, metastatic niche formation, and metastasis in a subset of breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…LOXL1 has been reported to play a role in pseudoexfoliation glaucoma and primary open angle glaucoma. LOXL3 and LOX4 have been implicated in breast cancer invasion and head and neck squamous cell carcinoma (15,38). ECM accumulation is now considered to play a more mechanistic role in the development of compromised barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting result came from a Spanish group. They used fluorescence in situ hybridization and showed that increased copies of the LOXL4 gene locus on chromosome 10q24 were associated with a higher invasiveness and frequency of lymph-node metastasis in head and neck cancer (Görögh et al, 2007).…”
Section: Lox and Hypoxia/invasivenessmentioning
confidence: 99%